Shoot growth efficiency and production of Quercus ilex L. in different climates (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).

Photosynthesis as a temperature indicator in Quercus ilex L. (Global and Planetary Change, 2000)
Net photosynthesis Pn , stomatal conductance gs , leaf temperature LT , transpiration rate . . . . E and in vivo chlorophyll fluorescence were monitored February 1996–February 1997 in Quercus ilex plants growing in the climax area Rome and . in the Garda lake region. Photosynthetic activity is an appropriate temperature-dependent functional trait linked to plant metabolism and performance. We employed photosynthesis as a stress temperature indicator. Regression analysis showed that in such regional climatic conditions, net photosynthetic rates were primarily correlated with temperature. The introduction of rainfall in the function did not significantly improve the theoretical prevision, in the range of temperature and rainfall analysed. The favourable leaf temperatures allowing 90–100% of the highest photosynthetic rates were 14–288C, decreasing over 50% when leaf temperature were respectively below 68C and over 378C: the low potential photochemical efficiency of 0.71 PSII Fv . rFm at Castelporziano during summer, confirmed the state of stress. Transpiration rates remained high with the increase of leaf temperature in summer, in spite of the 46% decrease of stomatal conductance. Nevertheless, this decrease allowed the maintenance of acceptable Pn rates in stressful conditions. The potential productivity of Q. ilex lied on high peaks of activity during periods of lower evaporative demand and a rapid stomatal response to an increase in air temperature and soil water deficit. Although it is difficult to forecast Q. ilex productivity and plant structure, we may hypothesize its future presence in the Mediterranean Basin by the capability of vegetative activity in a wide range of temperatures, the high stomatal control in stressful conditions, the high plasticity index and water use efficiency WUE .

Relationship between leaf life-span and photosynthetic activity of Quercus ilex in polluted urban areas (Rome). (Environmental pollution (Barking, Essex : 1987), 2000)
Anatomical, morphological and physiological leaf traits of Quercus ilex in response to different traffic levels (high traffic level, type A sites; average traffic level, type B sites; control sites, type C sites) were analysed in Rome. Superficial leaf deposits were analysed comparing unwashed and washed leaf samples. Washing lowered Pb 61% in A, 54% in B and 27% in C. Sr, Fe, Cu, Zn and Al showed the same trend as Pb. The higher photosynthetic activity of 1-year-old leaves (Pn=7.0+/-2.9 micromol m(-2 )s(-1), average value) in A sites with respect to B sites (6.7+/-2.4 micromol m(-2 )s(-1)) and C sites (6.7+/-1.8 micromol m(-2 )s(-1)) seems to be related to higher stomatal conductance (g(s)=0.13+/-0.06 mol m(-2 )s(-1)), higher total chlorophyll content (Chl=1.57 mg g(-1)) and higher leaf thickness (L(T)=218.9 microm), particularly palisade parenchyma thickness (109.4 microm). Q. ilex showed, on average, 95% of 1-year-old leaves and rarely 2-year-old leaves in A and B sites; 77% 1-year leaves, 20% previous-year leaves and sporadic 3-year leaves in C sites. The enhanced leaf senescence in A sites is compensated by a stimulated shoot production (18% higher with respect to C sites); 25% increased specific leaf area seems to be compensatory growth occurring in order to increase the size of the assimilatory area. The inverse trend of leaf life-span and Pn seems to be Q. ilex' adaptive strategy in polluted areas.

Relationship between photosynthetic activity and chlorophyll content in an isolated Quercus ilex L. tree during the year (Photosynthetica, 1998)
The relationship between chlorophyll (Chl) content and net photosynthetic rate (PN) in an isolated Quercus ilex tree, growing inside Villa Pamphili Park in Rome, was explored. The highest Pn was in March, May and September (10.1 umol.m-2.s-1, maximum rate). Pn decreased by 65% (with respect to the yearly maximum) when leaf temperature reached 34ºC, and by 50% when leaf temperature was 9ºC. The highest Chl contents were in April, October [1.47g.kg-1 (d.m.), maximum value], and December. The lowest Chl content was found in July (0.78 g.kg-1). The decrease of PN in July was in close connection with the decrease of Chl content. On the contrary, the high Chl content during winter did not correspond with PN of this season. Discordances between Chl content and PN over the year influenced the regression analysis, which although positive did not show very high correlation coefficients (r=0.79. The high Chl (a+b) content during most of the year indicated that the photosynthetic apparatus remained basically intact also during stress periods.

Morphological adaptions of Quercus ilex leaves in the Castelporziano forest (Plant Ecology, 1992)
The annual course of vegetative growth of the most representative species of a Ouercus ilex L. forest in Castelporziano (Latium, Italy) was studied through periodical analysis of selected ecophysiological leaf indexes, for the period 1987-1990. The results demonstrate that the local climate facilitates continuous vegetative activity of the sclerophyllous species without a latent phase. The variable morphology of sun and shade leaves of (2- ilex illustrates the plant's response to environmental stress.